THE EFFECT OF SPORT ON STUDENTS' SOCIAL ATTITUDES AND CHARACTER: A BIBLIOMETRIC STUDY OF ATTITUDE EDUCATION RESEARCH - Nurinnisa O, Aulia; Fitri, Mustika; Apriady, Hilmy (STKIP Singkawang, 2024)
This study examines the impact of sports attitude education on students' social attitudes and character through a bibliometric analysis of related literature. Using data from Scopus, the study identifies publication trends, influential authors, and popular keywords in sports attitude education from 2014 to 2024, encompassing 1,528 articles. The findings indicate that sports education significantly contributes to students' character development, emphasizing the importance of sports in education to support their social and personal growth. Additionally, the study finds that certain countries, such as the United States and the United Kingdom, maintain strong academic collaborations in this field. These findings provide insights for researchers and practitioners on the importance of integrating sports into school curricula to foster positive attitudes and character development in students